Risk of Depression after 5 Alpha Reductase Inhibitor Medication: Meta-Analysis - Kim, Jae Heon; Shim, Sung Ryul; Khandwala, Yash; Del Giudice, Francesco; Sorensen, Simon; Chung, Benjamin I. (The world journal of men's health, 2020)
Although five-alpha reductase inhibitor (5-ARI) is one of standard treatment for benign prostatic hyperplasia (BPH) or alopecia, potential complications after 5-ARI have been issues recently. This study aimed to investigate the risk of depression after taking 5-ARI and to quantify the risk using meta-analysis. A total of 209,940 patients including 207,798 in 5-ARI treatment groups and 110,118 in control groups from five studies were included for final analysis. Inclusion criteria for finial analysis incudes clinical outcomes regarding depression risk in BPH or alopecia patients. Overall hazard ratio (HR) and odds ratio (OR) for depression were analyzed. Moderator analysis and sensitivity analysis were performed to determine whether HR or OR could be affected by any variables, including number of patients, age, study type, and control type. The pooled overall HRs for the 5-ARI medication was 1.23 (95% confidence interval [CI], 0.99-1.54) in a random effects model. The pooled overall ORs for the 5-ARI medication was 1.19 (95% CI, 0.95-1.49) in random effects model. The sub-group analysis showed that non-cohort studies had higher values of HR and OR than cohort studies. Moderator analysis using meta-regression showed that there were no variables that affect the significant difference in HR and OR outcomes. However, in sensitivity analysis, HR was significantly increased by age (p=0.040). Overall risk of depression after 5-ARI was significantly not high, however its clinical importance needs validation by further studies. These quantitative results could provide useful information for both clinicians and patients.